New technologies in oral radiology as a diagnostic aid for monostotic fibrous dysplasia: a review - Torrico-Acha, Ximena (2021)
Monostotic fibrous dysplasia is a benign asymptomatic lesion that affects only one bone, which is replaced by amorphous connective tissue. Clinically there is an increase in the volume of the affected area, which is observed by imaging as a radiopaque area with diffuse non-corticalized limits capable of expanding to neighboring structures, and it is histologically evidenced as “resembling Chinese characters”. The lesion is seen as a radiopaque image with diffuse borders in conventional or digital radiography, while cone beam computed tomography identifies the exact location and extension of an isodense, mixed or hyperdense image of non-corticalized edges. Magnetic resonance imaging is also used when the lesion involves soft tissues or nerves, and bone scintigraphy is performed in order to systemically observe bone quality. The objective of this article was to describe the new technologies in oral radiology for the diagnosis of monostotic fibrous dysplasia and the importance of the current imaging methods in achieving an adequate diagnosis. These techniques range from conventional radiography to bone scans, which provide images of higher quality, clarity and better precision with less invasive techniques to the patient. This review of the literature helps to expand the knowledge of dental professionals in relation to the clinical and imaging characteristics of monostotic fibrous dysplasia.